USING AN INTEGRAL APPROACH TO ASSESSING THE COMPETITIVENESS OF IT COMPANIES - CHATCHENKО, Olga; VOROHOB, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the concept of "enterprise competitiveness" by various scientists and determines that the enterprise's competitiveness is the enterprise's ability to develop and the ability to produce goods or offer services that meet the requirements of the industry market under the condition of the best possible use of all available resources. An algorithm for assessing the competitiveness of the enterprise using an integral approach is proposed, which is formed according to the system of evaluation indicators of its activity in the following functional blocks: a block of indicators of financial potential; block of indicators of production potential; block of indicators of organizational potential and management. Approbation of the proposed approach was carried out based on the materials of telecommunications enterprises: PJSC "Kyivstar", PJSC "VF Ukraine", JSC "Ukrtelecom", LLC "Lifesell", which offer the same type of services, focusing on the same consumers, because of this, quite complex competition is formed. A general conclusion was made about the competitive advantages of Kyivstar PJSC among other enterprises in the field of telecommunications due to investments in the development of a mobile network that covers all large and small cities of Ukraine, as well as over 28,000 rural settlements, all main national and regional routes, most sea and river coasts.Therefore, the use of an integral approach to assess the competitiveness of a telecommunications company is a continuous process of transformation, as a result of which it is possible to note changes in the indicators of the company's functioning and highlight the advantages that primarily distinguish it from other competitors that offer similar products or services. Also, it contributes to the timely determination of the strategy for achieving competitive advantages, taking into account its position in the industry, goals, opportunities and resources.
Keywords: competitiveness; IT enterprises; integral indicator; competitive advantages; system of evaluation indicators